Identificação de padrões alimentares em uma população adulta: associação com marcadores de risco cardiometabólicos - Lopes, Elisama Costa (Universidade Federal do Tocantins, 2018)
The social, economic, demographic, technological and cultural changes that the country faced, especially since the middle of the last century, directly affected the food pattern, which has been constituted of food of high energy content and poor in nutrients, configuring a risk diet for obesity and cardiovascular diseases (CVD). Knowing the dietary patterns is important as a starting point for establishing relationships between food and health / disease and preventive and / or therapeutic interventions. Initially, a literature search was carried out in a systematized manner in the Medline (Medical Literature Analysis and Retrieval System Online), Lilacs (Latin American and Caribbean in Health Sciences) and SciELO (Scientific Electronic Library Online) , from original articles that identified a posteriori dietary patterns, between 2007 and 2017, in English, Spanish and Portuguese, having as descriptors: diet, dietary patterns, risk, cardiovascular, biomarkers, health and adult. Thirty-five studies were included. "Healthy", "traditional" and "prudent" patterns were associated with a better biochemical, anthropometric and blood pressure profile. On the other hand, the "Western", "Meat and alcohol" and "Snacks, fast food and desserts" patterns were directly associated with cardiometabolic risk. These results were the basis for a cross-sectional study with 130 adult male and female employees from a public university in Tocantins, Brazil, to identify dietary patterns, and to investigate associated demographic, socioeconomic, behavioral and cardiometabolic factors. Anthropometric measures, biochemical tests and blood pressure were measured, as well as interviews with sociodemographic, economic and behavioral data. Dietary patterns were identified by principal component analysis with orthogonal Varimax rotation, based on a food frequency questionnaire. Three patterns were identified: (1) healthy (fruits, vegetables, oats / granola, cereals / roots, chicken / fish, oilseeds, mixed cereal / root preparations and meats, eggs, pulses and natural juices); (2) western (breads, cakes, biscuits, sweets, beef, pork and meat offal, processed meats and bacon, whole dairy, soda, industrialized juices and feijoada) and (3) fit (butter, oilseeds, honey / sugarcane and eggs, and low consumption of margarine, soda and industrialized juices). After adjusting for sociodemographic, behavioral, anthropometric, biochemical and blood pressure variables, the healthy pattern was inversely associated with fasting glycemia, and directly with LDL-c, the western pattern was associated with higher concentrations of fasting glycemia and the fit pattern was inversely associated with LDL-c. Although the healthy dietary pattern was associated with higher concentrations of LDL-c, a fact that may have occurred due to reverse causality - a bias that is difficult to control in the cross-sectional design, it is recommended to encourage the adoption of this standard, mainly for foods with proven health benefits.